Kānsưksā rūpbǣp kānčhat kānrīanrū rabop sō̜ng phāsā (Thai-Malāyū) bǣp prayuk čhangwat chāidǣn Phāk Tai : rāingān kānwičhai - Mannī Phadungthaksin
Research report on pattern of learning management of Thai-Malayu languages for childhood schools in the three border Southern-most provinces of Thailand.